Selected Characteristics of Mothers as Related to Sex, Body Length and Weight of Newborns Delivered at the Voivodship Hospital of Białystok - Bogusłowicz , Wanda (Anthropological Review, 1983)
Material for the present study consisted of 2174 healthy firstborns delivered after 40 weeks of pregnancy in the years 1966, 1969, 1976 and 1979 at a hospital in the city of Białystok in Eastern Poland. Body length and weight of newborns were recorded together with age, blood group and menarcheal age of mothers. Increase of newborn body length during the period covered has been observed. No relations between observed characteristics of newborns and of their mothers have been found.